KAJIAN TERHADAP METODE DAN PENDEKATAN PEMBELAJARAN BIOLOGI DI SMA: KESENJANGAN DALAM PEMBELAJARAN DI KELAS - Rahmat, Adi (Jurnal Pengajaran MIPA, 2010)
The study on teaching and learning of biology class of senior high school was aimed to identify teaching methods and teaching approaches used by teachers in their lesson plans and its implementation in the classroom. The study was conducted in nine senior high schools including three categories of school based on the passing grade of school entrance. Data was collected by documentation study, classroom observation, questioner and interview. Result showed that most of teachers planed their class with four teaching approaches and six teaching methods. The four teaching approaches were conceptual approach, process skill approach, inquiry, and environmental approach where as the six teaching methods were speech, discussion, question and answer, demonstration, experiment, and assignment. In the reality there was a gap between lesson plan and the teaching practice in the classroom. Although teacher planed their lesson using several teaching approaches the instructional systems delivered by teachers in the classroom were more conceptual and were conducted to give the students more subject matter. This type of teaching and learning was categorized by students as a common teaching and was disliked by some students. The comfort of the biology class sensing by student was due to the content of the subject matter which is very close to the human life rather than by the instructional systems delivered by teacher.